Isolamento, tipificação e genotipagem de Brucella abortus isoladas de bovinos no Brasil - Silvia Minharro Barbosa (2009)
The aims of the present study were (i) to evaluate isolation methods for Brucella spp. and (ii) to biotype and genotype B. abortus isolates from cattle in Brazil, in order to support the Programa Nacional de Controle e Erradicação de Brucelose e Tuberculose (National Program on the Control and Erradication of Brucellosis and Tuberculosis) (PCNEBT). Enrichment using tryptose broth supplemented with Farrel antimicrobials increased the isolation rate of Brucella spp. 51.36% in clinical material from slaughterhouses (74/187) versus direct plating (36/187). Most of isolates were obtained after 7-day enrichment. From 137 Brazilian B. abortus isolates (from 1977 to 2008) biovars 1, 2, and 3 were confirmed and biovars 4 and 6 were identified for the first time. All biovar 3 isolates were classified as subgroup 3b by AMOS-ERY PCR. Three biovar 3 isolates from State of Pará amplified in AMOS PCR and could become an epidemiological marker. MLVA16 panel 1 identified two cluster (I and II): one that mainly clusters around genotype 40 strains and another that clusters around genotype 28. MLVA16 panels 2A and 2B showed high diversity among the 137 studied strains, identifying 89 genotypes. MLVA16 helped knowing the distribution of genotypes and will help to build a Brazilian B. abortus genotype database